Global trends in nature's contributions to people - Brauman, Kate A. (2020)
Declining biodiversity and ecosystem functions put many of nature’s contributions to people at risk. We review and synthesize the scientific literature to assess 50-y global trends across a broad range of nature’s contributions. We distinguish among trends in potential and realized contributions of nature, as well as environmental conditions and the impacts of changes in nature on human quality of life. We find declining trends in the potential for nature to contribute in the majority of material, nonmaterial, and regulating contributions assessed. However, while the realized production of regulating contributions has decreased, realized production of agricultural and many material commodities has increased. Environmental declines negatively affect quality of life, but social adaptation and the availability of substitutes partially offset this decline for some of nature’s contributions. Adaptation and substitutes, however, are often imperfect and come at some cost. For many of the contributions of nature, we find differing trends across different countries and regions, income classes, and ethnic and social groups, reinforcing the argument for more consistent and equitable measurement.